Fishfaunistic research in River Rába - Keresztessy, Katalin (Acta Agraria Debreceniensis, 2007)
Althogether 37 fish species were subject to research in the three sections of River Rába between 2004 and 2005, of which 13 are protected. 15 fish species are reophil occuring on the upper-section. In this period 6 adventiv fish species were collected.